Bullying Dengan Kekerasan Fisik Sebagai Pelanggar Hak Dasar - Nurhidah Sarifah (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Juvenile delinquency today is a very popular issue, this is related to the actions they take that have a negative impact. Bullying is one example of juvenile delinquency caused by poor family and play environment, it is classified as an act of violence that threatens the mentality of the victims of bullying. As a result of bullying, victims can have suicidal intentions due to the trauma they experience. The biggest impact experienced can certainly be done because of bullying with physical violence and on an ongoing basis. So with the problems that destroy children as state assets, this makes the task that must be resolved by the state because it intersects with basic rights as rights related to human rights themselves. The method used in examining this research is juridical normating with data collection by literature study, with the result that bullying is an act of juvenile delinquency that violates the basic rights of others and is very detrimental.